Peran Patroli Unit Turjawali Satuan Sabhara Dalam Mencegah Premanisme Di Wilayah Hukum Polresta Cirebon - Yoga Septian (Indonesian Journal of Police Studies, 2020)
The increasing number of thugs in the jurisdiction of Cirebon Police has an impact on the situation and conditions in the community. In some places there are a lot of thuggery problems, such as in the market, a red light. This research was conducted to find out the description of Thuggery in the Cirebon Police jurisdiction, factors that influence the implementation of the Turjawali Sabhara task force in dealing with thuggery and how the patrol unit of the Sabhara unit's Turjawali unit prevents thuggery in the Cirebon Police area. The theories are used are management theory, the concept of Patrol and the concept of thuggery. To optimize the implementation of the Sabjawali Turjawali unit in the framework of preventing thuggery in the Cirebon Police jurisdiction, researchers used management theory, patrol concepts and thuggish concepts. The approach taken by the researcher is a qualitative approach, from this researcher certainly can know the real picture by observation, interview and document review. The findings obtained by the author at the time of research in Cirebon Police are the number of cases of thuggery in 2019, the Turjawali Sabhara unit in Cirebon Police has carried out preventive, pre-emptive and repressive measures, and at this time is proven to be proven due to factors that Influence As the number of members is lacking, facilities and infrastructure are still lacking and need some or more ways to increase the need for acts of thuggery in the jurisdiction of the Cirebon Police. From the findings of research in the field, the authors recommend that the Cirebon Police Chief, Kasat Sabhara, and patrol members of the Turjawali unit of the Cirebon Sabrang Police Unit to implement patrol management, increase the number of members, apply management in the implementation of patrols starting with proper planning, organizing members, implementation in accordance with procedures and supervision of members in the field. It is intended that activities can be carried out effectively and efficiently.